INFECTION ASSOCIATED WITH THE IMPLANTATION OF CARDIOVASCULAR IMPLANTABLE ELECTRONIC DEVICES - L. I. Dvoretsky; R. M. Vakoluk; A. K. Kaptaeva; S. A. Doroshuk (Архивъ внутренней медицины)
Data on the frequency, nature, risk factors and diagnosis of infectious complications (IC) in patients with cardioimplanted electronic devices (CED) — artificial rhythm drivers, cardiodefibrillators, devices for cardiosynchronizing therapy — often prognostically unfavorable, accompanied by high mortality, are given in the article. The data of a large-scale retrospective analysis of 200 219 patients with CED are given during the 3-year period after implantation. It was noted that among persons with IC there was a higher mortality rate compared to patients without signs of infection. In the analysis of cases of IC, the main risk factors for their development are identified, including. Presence of concomitant pathology. This article discusses the basic types of microorganisms were isolated from patients with the presence of IC, IC clinical symptoms, provides a diagnostic algorithm for suspected IC. A feature of the clinical case presented in the article is a relatively early development of IC with damage to the valve structures (tricuspid valve) — the first symptoms of bacterial damage appeared 6 months after the operation. Usually infectious endocarditis in patients with CED was verified at various times after implantation — from 1 to 72 months, and in most cases not earlier than 3 months later. The main clinical manifestations of the disease were recurrent fever, which is why the patient was repeatedly hospitalized for several months in various medical institutions. In each hospital, the patient management tactics were different and did not meet the accepted standards of diagnostic search in a febrile patient with CED. Only with the third hospitalization of the patient (November 2015) during the transthoracic echocardiography were revealed vegetations on the valves of the tricuspid valve. The given clinical observation testifies not only to the difficulties of diagnosing IE in patients with the presence of CED, but also about the inevitable mistakes in maintaining this category of patients when the standards for diagnosis and treatment of IE are not complied with. The authors emphasize that in the course of diagnostic search, and later in the development of treatment tactics, it is necessary to follow the ESC Guidelines for the management of infective endocarditis in 2015.